Macrobenthic Community Structure as a Bioindicator of Environmental Quality at Pier 1, Kota Agung: Struktur Komunitas Makrobenthos sebagai Bioindikator Kualitas Lingkungan di Dermaga 1, Kota Agung - Pawhestri, Suci Wulan; Vantika, Marsela Ayu; Andandaningrum, Della; Ardianti, Indah Marlina (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2025)
This study aims to assess the water quality of Pier 1 Kota Agung using macrobenthic community structures as biological indicators. Coastal areas such as Kota Agung Pier are increasingly exposed to anthropogenic pressures due to port operations, shipping activities, and surrounding land use. These pressures can subtly alter water quality and benthic community structure over time. A descriptive quantitative approach was applied across three observation stations representing the aquatic conditions surrounding the pier. Macrobenthos samples were collected using a Macrobenthic sample, which was carried out using a 10-inch core sampler and a 10mm mesh, for physical and chemical parameters. The identified macrobenthic organisms belonged to the classes Gastropoda, Oligochaeta, and Malacostraca, showing moderate diversity (H’ = 1.337–1.567), high evenness (E = 0.84–0.98), and low dominance (D = 0.24–0.37). The Family Biotic Index (FBI) values ranged from 3.81 to 3.86, indicating good water quality with low levels of organic pollution. Physical and chemical parameters such as temperature, water clarity, pH, and dissolved oxygen were within the standard quality thresholds. The study reveals that the environmental conditions at Pier 1 Kota Agung are relatively good, as indicated by balanced macrobenthic community structures and supportive physicochemical parameters.